Vitamin/Mineral Supplementation in Athletes - Grunewald, K.
Armstrong LE, Maresh CM (Apr 1996) Vitamin and mineral supplements as nutritional aids to exercise performance and health. Nutr Rev. 54(4 Pt 2):S149-58. Bazzarre TL, Scarpino A, Sigmon R, Marquart LF, Wu SM, Izurieta M (Apr 1993) Vitamin-mineral supplement use and nutritional status of athletes. J Am Coll Nutr. 12(2):162-9. Beaton LJ, Allan DA, Tarnopolsky MA, Tiidus PM, Phillips SM. (May 2002) Contraction-induced muscle damage is unaffected by vitamin E supplementation. Med Sci Sports Exerc. 34(5):798-805. Belko AZ (Oct 1987) Vitamins and exercise--an update. Med Sci Sports Exerc. Oct;19(5 Suppl):S191-6. Beltz SD, Doering PL (Dec 1993) Efficacy of nutritional supplements used by athletes. Clin Pharm. 12(12):900-8. Benardot D, Clarkson P, Coleman E, Manore M (2001) Can vitamin supplements improve sport performance Gatorade Sport Science Institute Sports Science Exchange Roundtable 45(12) Clarkson PM (Summer 1991) Minerals: exercise performance and supplementation in athletes. J Sports Sci. 9 Spec No:91-116. Clarkson PM (Summer 1995) Micronutrients and exercise: anti-oxidants and minerals. J Sports Sci. 13 Spec No:S11-24. Clarkson PM, Haymes EM (June 1995) Exercise and mineral status of athletes: calcium, magnesium, phosphorus, and iron. Med Sci Sports Exerc. 27(6):831-43. Craciun AM, Wolf J, Knapen MH, Brouns F, Vermeer C (Oct 1998) Improved bone metabolism in female elite athletes after vitamin K supplementation. Int J Sports Med. 19(7):479-84. 9). Faber M, Benade AJ (June 1991) Mineral and vitamin intake in field athletes (discus-, hammer-, javelin-throwers and shotputters). Int J Sports Med. 1991 Jun;12(3):324-7. Fogelholm M (Dec 1995) Indicators of vitamin and mineral status in athletes' blood: a review. Int J Sport Nutr. 5(4):267-84. Fogelholm M (Summer 1994) Vitamins, minerals and supplementation in soccer. J Sports Sci. 12 Spec No:S23-7. Grandjean AC (Mar 1983) Vitamins, diet, and the athlete. Clin Sports Med. 2(1):105-14. Guilland JC, Penaranda T, Gallet C, Boggio V, Fuchs F, Klepping J (Aug 1989) Vitamin status of young athletes including the effects of supplementation. Med Sci Sports Exerc. 21(4):441-9. Haymes EM (June 1991) Vitamin and mineral supplementation to athletes. Int J Sport Nutr. 1(2):146-69. Itoh H, Ohkuwa T, Yamazaki Y, Shimoda T, Wakayama A, Tamura S, Yamamoto T, Sato Y, Miyamura M. (Jul 2000) Vitamin E supplementation attenuates leakage of enzymes following 6 successive days of running training.Int J Sports Med. 21(5):369-74. Kawai Y, Shimomitsu T, Takanami Y, Murase N, Katsumura T, Maruyama C. (Jun 2000) Vitamin E level changes in serum and red blood cells due to acute exhaustive exercise in collegiate women.J Nutr Sci Vitaminol. 46(3):119-24. Lukaski HC (June 1995) Micronutrients (magnesium, zinc, and copper): are mineral supplements needed for athletes? Int J Sport Nutr. 5 Suppl:S74-83. Lukaski HC, Nielsen FH. (May 2002) Dietary magnesium depletion affects metabolic responses during submaximal exercise in postmenopausal women. J Nutr. 132(5):930-5. McDonald R, Keen CL (Mar 1988) Iron, zinc and magnesium nutrition and athletic performance. Sports Med. 5(3):171-84. Massad SJ, Shier NW, Koceja DM, Ellis NT (Sept 1995) High school athletes and nutritional supplements: a study of knowledge and use. Int J Sport Nutr. 5(3):232-45. Moffatt RJ (Nov 1984) Dietary status of elite female high school gymnasts: inadequacy of vitamin and mineral intake. J Am Diet Assoc. 84(11):1361-3. Nielsen P, Nachtigall D (Oct 1998) Iron supplementation in athletes. Current recommendations. Sports Med. 26(4):207-16. Peters EM, Anderson R, Nieman DC, Fickl H, Jogessar V. (Oct 2001) Vitamin C supplementation attenuates the increases in circulating corticol, adrenaline and anti-inflammatory polypeptides following ultramarathon running. In J Sports Med. 22(7):537-43. Ronsen O, Sundgot-Borgen J, Maehlum S (Feb 1999) Supplement use and nutritional habits in Norwegian elite athletes. Scand J Med Sci Sports. 9(1):28-35. Rowland TW (Oct 1990) Iron deficiency in the young athlete. Pediatr Clin North Am. 37(5):1153-63. Schroder H, Navarro E, Mora J, Seco J, Torregrosa JM, Tramullas A. (Apr 2002) The type, amount, frequency and timing of dietary supplement use by elSite players in the First Spanish Basketball League. J Sports Sci. 20(4):353-8. Shephard RJ, Shek PN (1998) Immunological hazards from nutritional imbalance in athletes. Exerc Immunol Rev. 4:22-48. Singh A, Moses FM, Deuster PA (Jan 1992) Vitamin and mineral status in physically active men: effects of a high-potency supplement. Am J Clin Nutr. 55(1):1-7. Sobal J, Marquart LF (Dec 1994) Vitamin/mineral supplement use among athletes: a review of the literature. Int J Sport Nutr. 4(4):320-34. Sobal J, Marquart LF (Winter 1994) Vitamin/mineral supplement use among high school athletes. Adolescence. 29(116):835-43. Tauler P, Aguilo A, Fuentespina E, Tur JA, Pons A. (Mar 2002) Diet supplementation with vitamin E, vitamin C and beta-carotene cocktail enhances basal neutrophil antioxidant enzymes in athletes. Pflugers Arch. 443(5-6):791-7. Telford RD, Catchpole EA, Deakin V, Hahn AG, Plank AW (June 1992) The effect of 7 to 8 months of vitamin/mineral supplementation on athletic performance. Int J Sport Nutr. 2(2):135-53. Telford RD, Catchpole EA, Deakin V, McLeay AC, Plank AW. (June 1992) The effect of 7 to 8 months of vitamin/mineral supplementation on the vitamin and mineral status of athletes. Int J Sport Nutr. 2(2):123-34. van der Beek EJ (Summer 1991) Vitamin supplementation and physical exercise performance. J Sports Sci. 9 Spec No:77-90. Weight LM, Noakes TD, Labadarios D, Graves J, Jacobs P, Berman PA (Feb 1988) Vitamin and mineral status of trained athletes including the effects of supplementation. Am J Clin Nutr. 47(2):186-91. Weight LM, Myburgh KH, Noakes TD (Feb 1988) Vitamin and mineral supplementation: effect on the running performance of trained athletes. Am J Clin Nutr. 47(2):192-5. Williams MH (1989) Vitamin supplementation and athletic performance. Int J Vitam Nutr Res Suppl. 30:163-91. Williams MH (July 1984) Vitamin and mineral supplements to athletes: do they help? Clin Sports Med. 3(3):623-37. Zifferblatt SM (1993) Nutrition and fitness recommendations when science in transition. Vitamin and mineral supplementation: a case in point. World Rev Nutr Diet. 72:177-89. Review.